The Mediating Role of Meaningfulness in Work in the Relationship between Physical Environment, Social Environment and Job Satisfaction of Seafarers in Shipping Companies in Indonesia - Kundori, Kundori; Sukrisno, Sukrisno; Fauziningrum, Endah (Universitas Tanjungpura, 2026)
There is still no empirical study that integrates the meaningfulness of work as a mediating mechanism between the work environment (physical and social) and seafarers' job satisfaction, considering differences in ship levels as an important factor. This study aims to comprehensively examine the dynamics of Indonesian seafarers' job satisfaction by considering the role of the physical environment, social environment, and meaningfulness of work in the national shipping industry. This study uses a quantitative cross-sectional design. The data collection method is based on a structured questionnaire. Data analysis was conducted using AMOS 25. The results show strong empirical support for all proposed hypotheses. The effect of the Physical Environment on Meaningfulness in Work shows a path coefficient of 0.724 with a critical ratio of 8.967. Furthermore, the effect of Meaningfulness in Work on Job Satisfaction shows the highest coefficient of 0.795 with a critical ratio of 9.423. Testing the mediation effect through the Sobel test shows a Z value of 7.234 and 6.891 with a significance of p < 0.001. These findings support the Existence-Relatedness-Growth (ERG) framework, which emphasizes the importance of fulfilling basic needs, social needs, and growth needs in creating job satisfaction. It concludes that shipping companies must develop a comprehensive strategic approach to managing employee experience by integrating physical environment optimization, social environment enhancement, and meaningfulness cultivation as three mutually reinforcing pillars